ENTREPRENEURSHIP EDUCATION IN MALAYSIA: A CRITICAL REVIEW - Rahim, Hardy Loh; Abdul Kadir, Mohd Ali Bahari; Zainal Abidin, Zanariah; Junid, Junainah; Mohd Kamaruddin, Laila; Mohd Lajin, Noor Faizah; Buyong, Siti Zahrah; Ahmad Bakri, Adlan (Journal of Technology Management and Business, 2015)
Recognising the importance of entrepreneurship education in promoting entrepreneurship development and the economy, Malaysia Ministry of Higher Education has taken the initiative by making entrepreneurship subjects compulsory to all students at the nation public universities.Â  At the same time, these students are encouraged to take part in the many entrepreneurship activities at their respective universities - trainings, seminars, short courses, conferences and entrepreneurship events. The results of the effort can lead to less unemployed graduates and an increase in business opportunities, which will have a direct impact on achieving the developed nation status as envisioned by Malaysians. The entrepreneurship education in Malaysia is moving forward towards the right direction however issues and challenges still persist. This paper aims to review the entrepreneurship education in Malaysia by discussing the current situation of entrepreneurship education, the issues and challenges and recommending ways to improve the situation.